MOBILE EMERGENCY SERVICES: THE ACTIONS OF THE NURSING TEAM IN SITUATIONS OF VIOLENCE - Camargo, Fernanda Carolina; Alves Garcia, Luan Augusto; Rodrigues de Lucena, Ana Carolina; Iwamot, Helena Hemiko; Souza, Regiane Maximo de [UNESP]; Zullo, Sergio Antonio; Santos, Alvaro da Silva (Univ Federal Uberlandia, 2019)
This study aimed to evaluate the profile of attention of the mobile emergency services in cases of violence and the actions of the nursing team. Observational, exploratory and analytical study were undertaken from secondary records. A Correspondence Analysis was conducted to identify the associations between the actions of the nursing team and the profile of the necessity of care due to violent causes. The results showed that from 1800 cases, most took place during the weekend (49.2%), involving men (70.0%) and traffic accidents (76.5%). The correspondence analysis highlighted two dimensions (76.7% of explanatory contribution), resulting in three similar groups considering the nursing professional taking part in the attention, how the situation ended, period in which it occurred, and profile of the victim. The performed analysis was strategic for the systematization of data which gave support to the situational understanding of the composition of the service and for the planning of the actions of the nursing team.
Keywords: Emergency Medical Services; Emergency Nursing; Nursing Team; External Causes; Violence